3204 Renin-Angiotensin System Inhibitors Do Not Improve Survival in Fibrillin-1 Hypomorphic Mice with Established Aortic Aneurysm. (27th March 2019) - Sheppard, Mary Burchett; Chen, Jeff Zheying; Rateri, Debra L.; Moorleghen, Jessica J.; Weiland, Mackenzie; Daugherty, Alan
Abstract : OBJECTIVES/SPECIFIC AIMS: Drugs to attenuate aortic growth are usually not initiated in patients with Marfan syndrome until aortic dilation is already present. Therefore, we measured the impact of drugs (the renin-angiotensin system inhibitors losartan and enalapril) on survival and thoracic aortic growth in a mouse model of Marfan syndrome when extensive aortic dilation was already present. METHODS/STUDY POPULATION: Male and female fibrillin-1 hypomorphic (FBN1 mgR/mgR) mice (n=10-12/group) were stratified into treatment groups by aortic diameter at 6 weeks of age to ensure an equivalent average aortic diameter in each group at the start of the study. Osmotic mini pumps filled with PBS (vehicle), enalapril (2 mg/kg/d), or losartan (20 mg/kg/d) were implanted subcutaneously into mice after stratification. Mini pumps infusing drug or vehicle were replaced every 4 weeks for a total duration of 12 weeks. Wild type littermates (n=10) were infused with PBS as a negative control to the Marfan mouse model. Ascending aortic diameters from male and female FBN1 mgR/mgR mice and their wild type littermates were assessed by ultrasound every 4 weeks from 6 to 18 weeks of age. Aortic diameters were measured luminal edge to luminal edge during diastole. RESULTS/ANTICIPATED RESULTS: 6 week old FBN1 mgR/mgR mice exhibited significantly dilated ascending thoracic aortas at study initiation compared to their wild type sex-matched littermates (in males: FBN1 mgR/mgR = 1.87 +/− 0.07mm, wild type = 1.23 +/− 0.07mm; p <0.001) (in females: FBN1 mgR/mgR = 1.56 +/− 0.07mm, wild type = 1.18 +/− 0.07mm; p <0.001). Baseline mortality of FBN1 mgR/mgR mice infused with PBS was 36% in male and 22% in female mice at the time of study termination. Within sex-matched mgR littermates, there was no significant difference in survival between groups treated with PBS, enalapril, or losartan after 12 weeks (p=0.224 for males, p=0.094 in females). In the same groups, no significant difference in maximum ascending aortic diameter was detected after treatment for 12 weeks (in males: PBS=2.69 +/− 0.19 mm, enalapril=2.04 +/− 0.27 mm, losartan=2.42 +/− 0.28 mm; p=0.24) (in females: PBS = 1.92 +/− 0.13, enalapril=1.89 +/− 0.31, losartan=1.98 +/− 0.17; p=0.86). Furthermore, aortic diameters in the FBN1 mgR/mgR mice were found to demonstrate sexual dimorphism. DISCUSSION/SIGNIFICANCE OF IMPACT: This research shows that losartan is not effective when administered after significant thoracic aortic dilation has already occurred in FBN1 mgR/mgR mice. This has important translational implications because losartan is usually not started in patients with Marfan syndrome until significant aortic dilation is already present. Therefore, more research needs to be done to determine the critical time period within which this medicine will be effective if given to patients. In addition, this research demonstrates that male FBN1mgR/mgR mice have a significantly larger aortic diameter than female FBN1mgR/mgR mice. This sexual dimorphism has recently been observed in patients with Marfan syndrome as well. Additional studies for understanding the mechanism underlying this sexual dimorphism have the potential to elucidate new therapeutic approaches for aortic disease.